Pengolahan Sampah Anorganik Menjadi Ecobricks Sebagai Upaya Pengurangan Sampah Plastik - Putriani, Rizha Bery; Hasani, Qadar; Reza, Muhammad (TAAWUN, 2024)
This community service aims to reduce plastic waste that is quite a lot in the environment around us, especially in Bumi Waras Village. With concrete commitments and actions, it is hoped that the problem of inorganic waste, especially plastic, can be overcome gradually, restore marine ecosystems, and improve the quality of life of local communities. The method carried out during service activities is lectures and discussions (theory and practice). Through this service activity, the community has been given socialization about the types of waste and how to handle plastic waste in eco-bricks. The evaluation of this activity found that the community better understands the importance of proper waste management so that the environment is not polluted. People in Bumi Waras Village can also make clean plastic waste to be used as ecobricks. Ecobricks can be useful goods that are certainly environmentally friendly.